(untitled) (Indian Journal of Animal Production and Management, 2014)
A study was conducted on broilers in two trials to estimate blood biochemical parameters during summer and winter season. Blood samples (32 nos) were collected from two birds (one male & one female) per replicate, before slaughtering. The result revealed that the glucose concentration was significantly (p<0.05) higher in male (191.96±5.14, 197.37±1.90) birds than in female birds in both winter and summer season. Irrespective of sexes, the total proteins concentration (3.15±0.18 & 3.09±0.01) was significantly (p<0.05) higher in winter than in summer. The albumin calcium, phosphorus, tri-iodothyronine and alkaline phosphatase did not differ significantly in different seasons. However, concentration differed significantly (p<0.05) in females (16.17±0.41 and 9.30±0.48 ng/ml) between the two seasons.